Balance assessment using multimodal sensory system - Wang, Guo Wei (2015)
Balance assessment done in a clinical setting has always been the preferred mode when it comes to evaluating a person’s ability to maintain his or her posture. However, it is not always feasible for a patient to be assessed under the supervision of a doctor. In this project, static balance of a subject can be captured and measured through integration of multiple devices, namely a pressure mat and smart phones. Through advancements in technologies, smartphones now have sensors such as accelerometers built into them. By using such built in sensors, balance assessment could be done in a home setting at the convenience of the patients, at any time they like. However, there are limitations to what smart phones can differentiate such as if the user is standing on one or two legs. To overcome such limitations, a framework was developed to integrate a computer application, smartphone and pressure mat together communicating via UDP, with the computer application as the main controller. This framework also provides a real time display of the data collected, together with a balance evaluation. To the best of our knowledge, there has not been any application using both smart phone and a pressure mat together. In this project, Center Of Mass (COM) and G force has been used as the basis for features extracted for balance evaluation. From the experiment, it is observed that the two features serve as a complement for each other. Experiment results also show that it is possible to perform evaluation of balance with just one second of data. It was also found that giving a visual representation of how the user was doing in real time encouraged the user in maintaining a better balance.